Catenary action on RC beams subjected to missing column scenario - Kuan, Ian U. (2010)
Progressive collapse is becoming a major issue globally after the collapse of Ronan Point apartment building (1968) and the recent one, World Trade Centre (2001). The ability to mitigate it has become a main concern. Alternate load path (ALP) method is widely used in current building codes and the ground wisdom is that it is the proven model for designing robust buildings. Catenary action is the last ALP to prevent progressive collapse due to the large deformations to mobilize it. In an extreme scenario whereby a column of a building has been destroyed, the load on top will seek an alternate load path. Beam-column sub-assemblage tests were carried out to find out the load-resisting mechanisms involved and transformed from one to another. The load resisting mechanisms are flexural action, compressive arch action and tensile catenary action, and which is the main interest in this research. During the sub-assemblage tests, three test specimens S4, S5, S7, designed by Yu Jun, were tested and the results were compared to find out how the change in bottom reinforcement and length of the specimen would affect the capacities of the three load-resisting mechanisms. From the force-displacement history, the capacity for each mechanism can be determined. Empirical formula modified by Yu Jun would then be used to calculate the capacity of the compressive arch action capacity to compare with the experimental results.